2014
DOI: 10.1016/j.jcot.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Neglected post burns contracture of hand in children: Analysis of contributory socio-cultural factors and the impact of neglect on outcome

Abstract: Methods: 66 hands in 61 children (mean age 12.22 years) with a mean neglect of 11.6 years (range 5e17 years) were assessed for the causes of neglect and the outcome of surgery.Average follow up was 6.6 years. The results were assessed in two groups of 5e10 years neglect as group I and >10 years neglect as group II.Results: In a total number of 134 contracted rays in 66 hands, the surgical procedures included local Z/V-Y flap (51 rays), cross finger flap (48 rays), full thickness graft (35 rays).Additional exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
1
9
0
3
Order By: Relevance
“…Gupta RK et al (2014) in their study also observed male female ratio of 1.03. [8] Our study is in concordance with the other studies. The preponderance of males over females may be due to the fact that males whether children or adults are more adventurous and more prone to injury and also that they are the bread earners of the family and thus morbidity affecting them is taken seriously and medical care is sorted, while the females are ignored.…”
Section: Age In Yearssupporting
confidence: 94%
See 3 more Smart Citations
“…Gupta RK et al (2014) in their study also observed male female ratio of 1.03. [8] Our study is in concordance with the other studies. The preponderance of males over females may be due to the fact that males whether children or adults are more adventurous and more prone to injury and also that they are the bread earners of the family and thus morbidity affecting them is taken seriously and medical care is sorted, while the females are ignored.…”
Section: Age In Yearssupporting
confidence: 94%
“…Gupta RK et al [8] in their study also found that right hand was more commonly involved (60.65%). It is quite natural, since most of the people are right-handed and thus it has a greater chance of injury and thus contracture.…”
Section: Age In Yearsmentioning
confidence: 75%
See 2 more Smart Citations
“…The severity of a burn contracture depends on factors like the location and the depth of the burn, the time of surgical or nonsurgical treatment, post-injury splinting, hand therapy and scar care during the maturation process. 3 McCauley designed a severity rating for burn contractures of the hand by grading them I to IV. 4,5 Grade 1 and 2 contractures can be managed with typical therapy while grade III and IV contractures are further subcategorized as flexion, extension and mixed deformities.…”
mentioning
confidence: 99%